Hubungan Cyberloafing dan Stres Kerja Pada Pegawai Negeri Sipil di Aceh Barat - Cindy, Frisca Amara; Zhafira, Nabila Hilmy; Damrus, Damrus; Rusdi, Rusdi (Jurnal Ilmiah Ekonomi Terpadu (Jimetera), 2025)
In this study, Civil Servants were more involved in light cyberloafing activities, such as chatting on WhatsApp and accessing social media platforms like Instagram, Twitter, and Facebook, while more serious forms of cyberloafing were not found in the office. The main objective of this research was to identify the relationship between work stress levels and cyberloafing behavior among Civil Servants in West Aceh. The research method used was a quantitative approach with data collection through a questionnaire. The population studied consisted of 372 employees, with a sample size of 80 employees calculated using the Slovin formula. The data was analyzed using the Pearson Product Moment Correlation technique, processed with SPSS 20.0 for Windows. Prior to this, validity and reliability tests were conducted to ensure the validity of the data used. Normality and linearity tests were also performed. Based on the research results, the questionnaire used was found to be valid and reliable. Descriptive results showed that the majority of respondents experienced high work stress and cyberloafing behavior. Hypothesis testing with Pearson Correlation revealed a very strong positive relationship between work stress and cyberloafing behavior, with the test results showing a p-value < 0.05 (0.000) and an accuracy strength of 0.955. This study indicates that the higher the level of work stress, the higher the level of cyberloafing among Civil Servants in West Aceh. Both hypotheses proposed in this study were accepted. The study also found that work stress and cyberloafing influence each other, where an increase in work stress leads to an increase in cyberloafing, and vice versa.